2017
DOI: 10.1002/mnfr.201700473
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Dietary Fiber Reduces Trimethylamine Metabolism via Gut Microbiota and Co‐Regulates Host AMPK Pathways

Abstract: These findings suggest a central mechanism via which SDF-diet may control TMA metabolism by gut microflora and co-regulate the AMPK pathways of the host.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 50 publications
2
46
0
Order By: Relevance
“…Interestingly, weaker intestinal epithelial AMPK β expression levels indicated by low fluorescence intensity observed in the immunoblot image were observed in the red meat diet group compared to those in the fiber-rich diet groups (Figure 5c). This is consistent with our previous observation that a diet rich in red meat can inhibit AMPK expression levels (Li et al, 2017). The distance-based redundancy analysis (RDA) ordination plots illustrated the relationship between the differences observed in the CAZyme gene family profile of gut microbiota genomes with environmental variable (Figure 5d).…”
Section: Analysis Of Gene Family Profiles From the Cazy Database Ofsupporting
confidence: 90%
See 2 more Smart Citations
“…Interestingly, weaker intestinal epithelial AMPK β expression levels indicated by low fluorescence intensity observed in the immunoblot image were observed in the red meat diet group compared to those in the fiber-rich diet groups (Figure 5c). This is consistent with our previous observation that a diet rich in red meat can inhibit AMPK expression levels (Li et al, 2017). The distance-based redundancy analysis (RDA) ordination plots illustrated the relationship between the differences observed in the CAZyme gene family profile of gut microbiota genomes with environmental variable (Figure 5d).…”
Section: Analysis Of Gene Family Profiles From the Cazy Database Ofsupporting
confidence: 90%
“…DF was extracted from fermented wheat bran prepared by inoculation with Rhizopus oryzae (obtained from biology laboratory in Tianjin University of Science and Technology) as described previously (Li, Wu, Liu, Zhang, & Wang, 2017). DF was extracted from fermented wheat bran prepared by inoculation with Rhizopus oryzae (obtained from biology laboratory in Tianjin University of Science and Technology) as described previously (Li, Wu, Liu, Zhang, & Wang, 2017).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Red meat consumption increased systemic TMAO levels, but high versus low levels of saturated fat in the context of a red meat diet did not affect plasma TMAO or TMAO precursors [24]. Li et al (2017) investigated the effect of soluble dietary fiber on TMA metabolism in mice fed red meat and found that soluble dietary fibers reduced TMA and TMAO metabolism and modified the gut microbiota in mice fed with red meat [25]. Background diets in the present study were characterized by a complex composition and varied in several parameters.…”
Section: Background Diet Affects Urinary Tmao Excretion Following Redmentioning
confidence: 91%
“…Thus, the high content of fruits and vegetables in the prudent background diet might contribute to the attenuation of TMAO formation. Likewise, the higher fiber content in the prudent background diet may lead to a reduced TMAO formation [25]. Only a few studies have investigated the effect of red versus white meat consumption on urinary TMAO excretion, and urinary TMAO levels do not necessarily correspond to plasma TMAO levels as shown, for example, by Bielinska et al (2018) [34] and Jakobsen et al (2017) [15].…”
Section: Background Diet Affects Urinary Tmao Excretion Following Redmentioning
confidence: 99%